Treatment options for large posterior restorations: Systematic review and Meta-Analysis - Saud Fahad Al Abdulwahed,; Mohammed Abdulrahman Alqahtani,; Sultan Abdulkarim Bindayel,; Omar Khalid Alqasoumi,; Saad Saud Almugren,; Abdulmajeed Olayan Alenazi,; Alissa, Abdulrahman Saleh; Abdurahman Alhissan,; Mashael Abdullah Alfozan,; Nawaf Fahad Alsudairi, (International Journal of Medical Toxicology and Legal Medicine, 2024)
Background: There is an indication of rising costs for dental care over time, primarily due to the insertion and repair of restorations. The most effective therapy approach for extensive care in permanent posterior teeth is still debated in dental literature. Aim:To investigate treatment options for large posterior teeth restoration. Materials and methods: Two authors performed separate searches of internet databases, including EMBASE, PubMed, Scopus, Cochrane Library, Web of Science &MEDLINE. The inclusion criteria have been determined by the PICOSelements. Population (P): posterior molars. Intervention (I): adhesively bonded indirect restorations. Comparison (C): direct restoration. Outcome (O): the duration until the initial non-repairable or repairable restoration failure and the rate of annual failure. research design (S): Retrospective and prospective, (non-)randomized (un-)blinded clinical tests with a minimum monitoring duration of 3 years; Extractable information includes: quantity of repairs placed, evaluation of outcomes, and reasons for failure. Main findings and conclusion:A total of 512 articles have beendiscovered by electronic databases. Finally, eight RCTs have beenchosen. Our eight studies were conducted mainly in Germany, the Netherlands, Canada, and 4 other countries around the world, patients were subjected to different procedure and implants.Our pooled research revealed that direct resin composite exhibited better results for direct restorations, while gold was optimal for indirect restorations.Our pooled studies for AM Versus GI and DR Versus GI were homogenous. The pooled studies for DR versus AM were heterogenous with I2 99% and chi-p 0.019.